Clinical profile of ChAdOx1 nCoV-19- and BBV152-vaccinated individuals among hospitalized COVID-19 patients: a pair-matched study. (August 2022) - Keri, Vishakh C.; Arunan, Bharathi; Kodan, Parul; Soneja, Manish; Nischal, Neeraj; Varadarajan, Ashwin; Didwania, Akansha; R.L., Brunda; Aggarwal, Anivita; Jorwal, Pankaj; Kumar, Arvind; Ray, Animesh; et al.
Background: COVID-19 infections among severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-vaccinated individuals are of clinical concern, especially in those requiring hospitalization. Such real-world data on ChAdOx1 nCoV-19- and BBV152-vaccinated individuals are scarce. Hence, there is an urgent need to understand their clinical profile and outcomes. Methods: A 1:1 pair-matched study was performed among vaccinated and unvaccinated COVID-19 patients admitted between March 2021 and June 2021 at a tertiary care centre in New Delhi, India. The vaccinated group (received at least one dose of ChAdOx1 nCoV-19 or BBV152) was prospectively followed till discharge or death and matched [for age (±10 years), sex, baseline disease severity and comorbidities] with a retrospective group of unvaccinated patients admitted during the study period. Paired analysis was done to look for clinical outcomes between the two groups. Results: The study included a total of 210 patients, with 105 in each of the vaccinated and unvaccinated groups. In the vaccinated group, 47 (44.8%) and 58 (55.2%) patients had received ChAdOx1 nCoV-19 and BBV152, respectively. However, 73 patients had received one dose and 32 had received two doses of the vaccine. Disease severity was mild in 36.2%, moderate in 31.4% and severe in 32.4%. Two mortalities were reported out of 19 fully vaccinated individuals. All-cause mortality in the vaccinated group was 8.6% (9/105), which was significantly lower than the matched unvaccinated group mortality of 21.9% (23/105), p = 0.007. Vaccination increased the chances of survival (OR = 3.8, 95% CI: 1.42–10.18) compared to the unvaccinated group. Conclusion: In the second wave of the pandemic predominated by delta variant of SARS CoV-2, vaccination reduced all-cause mortality among hospitalized patients, although the results are only preliminary.